Support Mechanisms of Government and Commercial Banks in Strengthening Women Entrepreneurship. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study investigates the role of government schemes and commercial banks’ credit facilities in promoting women entrepreneurship in Kollam district, Kerala. It aims to identify the challenges women entrepreneurs face in accessing credit and financial services, and to evaluate the effectiveness of government-sponsored training and capacity-building initiatives. To achieve this, a survey was conducted among 50 women entrepreneurs in the district. The findings indicate that government schemes and commercial bank credit facilities have significantly contributed to the growth of women entrepreneurship in Kollam. However, women entrepreneurs continue to encounter major obstacles in securing financial support, particularly due to inadequate collateral, limited financial literacy, and discriminatory lending practices. The study recommends that both government agencies and commercial banks simplify loan procedures, provide collateral-free credit options, and expand training programs focused on financial literacy and business management. Overall, the study offers valuable insights for policymakers, financial institutions, entrepreneurs, and researchers committed to advancing women’s entrepreneurship and economic empowerment in India.